2010
DOI: 10.1111/j.1365-3164.2009.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose recombinant canine interferon-γ for treatment of canine atopic dermatitis: An open randomized comparative trial of two doses

Abstract: The purpose of this study was to investigate the minimum effective dose of recombinant canine interferon-gamma (rCaIFN-gamma) for the treatment of dogs with atopic dermatitis (AD). Thirty-four dogs with AD from 17 animal hospitals in Japan were administered half or one-fifth of the approved rCaIFN-gamma dose of 10 000 units/kg, three times a week for 4 weeks, followed by once weekly for an additional 4 weeks. Pruritus, excoriation, erythema and alopecia were evaluated and scored by the investigators on weeks 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 9 publications
0
30
0
3
Order By: Relevance
“…Current medical trials aimed to neutralize IL-17 or IL-23 have shown to be highly effective in humans in the treatment of psoriasis and show promising initial results in ankylosing spondylitis and multiple sclerosis [65]. These innovating therapies are now appearing in companion animal medicine [66] and should be considered in inflammatory autoimmune diseases like SRMA.…”
Section: Discussionmentioning
confidence: 99%
“…Current medical trials aimed to neutralize IL-17 or IL-23 have shown to be highly effective in humans in the treatment of psoriasis and show promising initial results in ankylosing spondylitis and multiple sclerosis [65]. These innovating therapies are now appearing in companion animal medicine [66] and should be considered in inflammatory autoimmune diseases like SRMA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been tested experimentally as an adjuvant in vaccines (20,21) and as a treatment in animal models of disease, such as tuberculosis (22), each with various degrees of success. Currently the only FDA-approved uses for IFN-␥ in humans are treatments for chronic granulomatous disease (23) and osteopetrosis (24), but IFN-␥ is also prescribed by veterinarians to treat canine atopic dermatitis (25). These clinical uses of IFN-␥ highlight its pleiotropic nature as the mechanisms of action in these diseases are through enhanced innate immunity, activation of osteoclasts, and suppression of the adaptive immune response, respectively.…”
mentioning
confidence: 99%
“…There are many treatment options available to practitioners for CAD including topical and systemic fatty acids . Polyunsaturated fatty acids have been shown to not only improve the skin barrier, but also decrease skin inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatment options available to practitioners for CAD including topical and systemic fatty acids. 1,12,14,[23][24][25][26][27] Polyunsaturated fatty acids have been shown to not only improve the skin barrier, but also decrease skin inflammation. 12,13,22,28 Thus, a topical product containing those agents may improve clinical signs and reduce the need for more potent medications.…”
Section: Discussionmentioning
confidence: 99%